Parenting Solutions As An Alternative To Reducing Stress Levels In Mothers In Childcare - Husniyyah, Haya Najma; Abdulkarem, Sumaiah Taleb (Program Studi Pendidikan Luar Sekolah FKIP Universitas Jember, 2024)
Mothers have great responsibilities within the family. Daily routines often leave them bored, leading to recurrent stress. This study aims to deeply understand how mothers feel, experience, and assess the parenting interventions they apply in an effort to reduce the stress they experience. Data were collected through primary data conducted by structured interviews using a questionnaire instrument. The results of the analysis show that the application of parenting as a solution in parenting can help reduce stress levels, increase satisfaction, and improve emotional well-being and the quality of the mother's relationship with the child